Filtered and graded Procesi extensions of rings - Radwan, A.E. (Algebra and Discrete Mathematics, 2007)
In this paper, we introduce filtered and graded Procesi extensions of filtered and graded rings as a natural modification of Procesi extensions of rings. We show that these extensions behave well from the geometric point of view.